On flavonoid accumulation in different plant parts: variation patterns among individuals and populations in the shore campion (Silene littorea) - del Valle, José C.; Buide, Ma L.; Casimiro-Soriguer, Inés; Whittall, Justen B.; Narbona, Eduardo (Frontiers in Plant Science, 2015)
The presence of anthocyanins in flowers and fruits is frequently attributed to attracting pollinators and dispersers. In vegetative organs, anthocyanins and other non-pigmented flavonoids such as flavones and flavonols may serve protective functions against UV radiation, cold, heat, drought, salinity, pathogens and herbivores; thus, these compounds are usually produced as a plastic response to such stressors. Although the independent accumulation of anthocyanins in reproductive and vegetative tissues is commonly postulated due to differential regulation, the accumulation of flavonoids within and among populations has never been thoroughly compared. Here, we investigated the shore campion (Silene littorea, Caryophyllaceae) which exhibits variation in anthocyanin accumulation in its floral and vegetative tissues. We examined the in-situ accumulation of flavonoids in floral (petals and calyxes) and vegetative organs (leaves) from 18 populations representing the species’ geographic distribution. Each organ exhibited considerable variability in the content of anthocyanins and other flavonoids both within and among populations. In all organs, anthocyanin and other flavonoids were correlated. At the plant level, the flavonoid content in petals, calyxes and leaves was not correlated in most of the populations. However, at the population level, the mean amount of anthocyanins in all organs was positively correlated, which suggests that the variable environmental conditions of populations may play a role in anthocyanin accumulation. These results are unexpected because the anthocyanins are usually constitutive in petals, yet contingent to environmental conditions in calyxes and leaves. Anthocyanin variation in petals may influence pollinator attraction and subsequent plant reproduction, yet the amount of anthocyanins may be a direct response to environmental factors. In populations on the west coast, a general pattern of increasing accumulation of flavonoids towards southern latitudes was observed in calyxes and leaves. This pattern corresponds to a gradual increase of UV-B radiation and temperature, and a decrease of rainfall toward the south. However, populations along the southern coast exposed to similar climatic stressors showed highly variable flavonoid contents, implying that other factors may play a role in flavonoid accumulation.